Political concepts - Bellamy, Richard (Manchester University Press, 2003)
Written by a powerful international team of theorists, this book offers a sophisticated analysis of the central political concepts in the light of recent debates in political theory. All political argument employs political concepts. They provide the building blocks needed to construct a case for or against a given political position. To address such issues as whether or not development aid is too low, income tax too high, or how to cope with poverty and the distribution of wealth, citizens must develop views on what individuals are entitled to, what they owe to others, and the role of individual choice and responsibility in these areas. These matters turn on an understanding of concepts such as rights, equality and liberty and the ways they relate to each other. People of different political persuasions interpret such key political concepts in different ways. This book introduces students to some of the main interpretations, pointing out their strengths and weaknesses. It covers a broad range of the main concepts employed in contemporary political and theoretical debates. Separate chapters look at liberty, rights, social justice, political obligation, nationalism, punishment, social exclusion, legitimacy, the rule of law, multiculturalism, gender, public and private, democracy, environmentalism, international justice and just war. This book is perfect for students of political theory and political ideology, and indeed anyone approaching political theory for the first time.